Beyond socialist camaraderie. Cross-border railway between German Democratic Republic, Poland and Soviet Union (1950s–60s). Issue 2 (August 2019) - Flade, Falk
In order to facilitate cross-border railway transport between socialist countries in Eastern Europe, the Council of Mutual Economic Assistance and later the Organisation for Cooperation of Railways were established in 1949 and 1956. Joint planning, standardisation and tariff policy were the main fields of cooperation. The paper focuses on the struggles between Council of Mutual Economic Assistance and Organisation for Cooperation of Railways member countries regarding transit tariffs for cross-border freight shipments. These struggles, dragging on for more than three decades, reveal the economic interests of individual member countries and the limitations of socialist foreign trade (and alleged friendship). This study argues that despite of political declarations and the establishment of socialist international organisations, the East European railways became a major bottleneck in intrabloc trade.